Gut Microbiome and Kidney Disease in Pediatrics: Does Connection Exist? - Vasylyeva, Tetyana L.; Singh, Ruchi (Frontiers in Microbiology, 2016)
Child development is a unique and continuous process that is impacted by genetics and environmental factors. Gut microbiome changes with development and depends on the stage of gut maturation, nutrition, and overall health. In spite of emerging data and active study in adults, the gut-renal axis in pediatrics has not been well considered and investigated. This review will focus on the current knowledge of gut microbiota impacts on kidney disease with extrapolation to the pediatric population.